The problem of fatigue in patients suffering from neoplastic disease - Kolak, Agnieszka; Kamińska, Marzena; Wysokińska, Elwira; Surdyka, Dariusz; Kieszko, Dariusz; Pakieła, Magdalena; Burdan, Franciszek (Contemporary Oncology/Współczesna Onkologia, 2017)
Modern therapeutic management of patients with cancer is associated with many adverse side effects, including fatigue defined as weariness, burnout, lassitude, malaise, apathy, impatience, and/or inability to perform daily activities. It occurs frequently before the diagnosis of cancer and may persist for a long time after the end of cancer therapy. It is a common problem that occurs regardless of the type of cancer and applied therapeutic procedure. The appearance of this symptom significantly affects the quality of life of patients and often reduces the effectiveness of implemented treatment. The symptom of fatigue occurs among approximately 80% of patients treated with chemotherapy and/or radiotherapy, as well as among more than 75% of patients with metastatic disease. Causes of fatigue include metabolic and immune system disorders as well as increased level of tumour necrosis factor  (TNF-). Recent studies also indicate a significant contribution of other cytokines, especially pro-inflammatory ones, i.e. interleukin-1 (IL-1), interleukin-6 (IL-6), soluble tumour necrosis factor receptor type II (sTNF type II) and C-reactive protein (CRP). A patient reporting fatigue should be properly diagnosed and thoroughly interviewed by doctors. Patients are mostly treated non-pharmacologically (by means of physical exercise and psychotherapy) and pharmacologically (by applying methylphenidate and methylprednisolone). What is also extremely important is proper education of the patient and their closest family/friends on the symptoms, which significantly reduces anxiety and stress. On the other hand therapeutic management hinders the subjectivity of feeling and lack of standardised scales to rate symptoms.